La carta de crédito y el crédito documentario frente a la normatividad local e internacional (2016)
The documentary credit or letter of credit is a conditional payment commitment assumed by the importer's bank in favor of the exporter, according to instructions received from his client (Cadena and Cubillos, 2006: p, 162). It is considered as the most secure means of payment (Ruiz, 2003: p, 1). The exporting company will charge at the agreed time, provided it presents documents in compliance. There are a number of incompatibilities in this means of payment at the national and international level, Colombian regulations establish it as an agreement that may be revocable contrary to international regulation. Faced with these differences, the international arbitration tribunals have had the task of solving the conflicts that have been present in these globalized contracting. Colombian law has a standard for this type of transactions, but allows the use of international standards, leaving it to the arbitration of those involved, being the contract law for the parties.